Sustainable development of the national economy – priorities, parameters and managdement instruments - Radev, Kiril Genadiev (Leadership, Society, Strategic Visions, 2021)
The report outlines the current characteristics and priorities of the management of sustainable development. Presented is an administrative regulatory framework for sustainable development. Defined are arguments on actual results of the implementation of the objectives of sustainable development in EU. An analysis of the priorities, policies and goals of the sustainable development of the Republic of Bulgaria has been made. Emphasis is placed on global insecurity, digitalisation and cybersecurity.